Prediction and optimization of tribological behavior of AlB2/Al composite according to Taguchi analysis approach - Savas, Omer; Inci, Erman (ELSEVIER, 2022)
Cylinders, pump parts, bearings and moving parts are expected to exhibit high wear resistance in engineering applications. For this purpose, wear-resistant AlB2-reinforced aluminum matrix composites have been produced and investigated their abrasive wear properties. Unlike other studies, it has been revealed how much the addition of AlB2 improves the wear properties, taking into account a large number of wear parameters, such as reinforcement ratio, abrasive media, applied load, sliding speed and distance. Experimental wear recipes have been created based on L-27(5(3)) array. It has been observed that the wear rate of the composites decrease with the increase in the reinforcement ratio. It was also determined that the addition of 15 wt%AlB(2 )improved the wear properties of the composites by 77%.
Keywords: AlB2; Taguchi; Wear rate; WEAR BEHAVIOR; RATIO; Materials Science; Physics